(untitled) (Research, Society and Development, 2020)
Launched in 2003, the National Humanization Policy (NHP) of SUS, also known as Humaniza SUS, aimed to provide improvements in care, adjusting the quality of care provided to the population, taking into account the practice of childbirth as one all. Thus, this study presented as main aim to understand the perception of puerperae women about the importance of nursing staff’s practice in the humanized vaginal delivery in a public maternity hospital in the Municipality of Imperatriz-MA. This is a descriptive study with a qualitative approach, carried out with 16 puerperae. For this, data were obtained through the application of a questionnaire structured during the months of november and december of 2018 and submitted to analysis and interpretation of the content. In this, three categories emerged: professional reception; partial techniques of humanization of childbirth; and the perception of puerperal women about childbirth care. Results showed that humanized nursing care during childbirth provides safety, comfort and emotional balance for parturient, thus, seeking to minimize pain through techniques and bring relaxation, which improves the quality of the delivery, not only for the nursing team, but mainly for the protagonist who is the woman; some techniques include: ambulation, baths, massages and use of swiss ball. Overall, according to the information obtained, it was possible to perceive partial humanization practices applied by the professionals, allowing these women to feel safer with their companions and to opt for methods they wanted to use so that their pains were minimized.